Prologica and the National Informatics Policy - Eiras, Marcelo Coradassi (Seven Editora, 2023)
The purpose of this article is to talk about Prologica Computadores, one of the largest microcomputer and peripheral manufacturing companies in the 1980s, which had its peak during the Brazilian Market Reserve (Federal Law 7232/84), its main products, R&D, reverse engineering, and the entire structure of several complementary companies. DOI:https://doi.org/10.56238/alookdevelopv1-015